Diseño de prototipo de vivienda para aprovechamiento en el marco del turismo rural en la ruta mágica del café - Motta Ortiz, Mateo (Universidad Antonio Nariño, 2023)
Between the Gigante and Garzón municipalities, located in the center of the department of Huila, "The magic coffee route" was formalized, an agro on the SilvaniaZuluaga tourist route made up of farmers located road that connects both town centers on the mountain range oriental, its purpose is to make visible and promote local development focused primarily on agrotourism and rural tourism as an additional offer to what they have in their territories and taking ad vantage of the outstanding and prominent place that Huila occupies as the first producer of specialty coffee nationwide; The services provided within this route are: lodgings, viewpoints, nature tourism, cultural tourism, agrotourism and cycling, the need for new accommodation is evident since the scenarios that make it up have a deficit of accommodation capacity and insufficiency in the already existing to accommodate visitors and potential guests. Through this project, the aim is to provide a rural housing solution that responds to the high demand that is beginning to arise from tourists who want to know and travel the route, and it is aimed mainly at those farmers who do not have prior knowledge of design and construction so that the prototypes made Keywords: serve as references for them.